SETTLEMENT OF LAND BOUNDARY DISPUTES BETWEEN INDONESIA WITH MALAYSIA (Institut Pemerintahan Dalam Negeri, 2021)
No country in the word that hasn’t boundaries with other country, the boundaries could be on land, air and sea. State boundaries on land is an important boundary, because most of the word’s populationliving on land. Indonesia has a land boundary with Malaysia in Kalimantan island. That land border is located in West Kalimantan and East Kalimantan. Indonesia and Malaysia land borders still have ten areas in disputes, five of which are located in West Kalimantan. This may occur because of the lack of agreement between the two countries. Vagueness of the legal basic between Indonesia and Malaysia regarding the land borders between two countries is one of the factors causing the border disputes can occur. This research attempts to analyze what it the basic of the land borders berween Indonesia and Malaysia in Kalimantan Island. The result are., the basic legal of land boundary between Indonesia and Malaysia is MOU 1973, that oriented to London Treaty which artificial y Dutch and English while still colonize Indonesia and Malaysia. In addition, this study also analyzes how to resolve land boundary disputes between Malaysia and Indonesia. Then the result obtained that negotiation is the appropriate way to resolve land boundary disputes between Malaysia and Indonesia.Keyword; Land Boundary, Kalimantan Island, Dispute Resolve